Pemberdayaan Perempuan melalui Inovasi Budidaya Ikan dalam Ember dan Strategi Pemasaran Digital - Indah Kusumawati, Weny; Muh. Bahruddin; Stephanie Astrid Ayu; Yunanto Tri Laksono; Charisma Dimas Affandi (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Limited land and low digital literacy are major problems for women in rural areas in developing productive economic activities. This Community Service Program (PkM) aims to empower members of the PKK (Family Welfare Movement) in Sidorame Hamlet, Gunungan Village, Dawar Blandong Subdistrict, Mojokerto Regency through the application of Internet of Things (IoT)-based Fish Farming in Buckets (Budikdamber) technology and Smart Online Marketing training. The implementation method uses a Participatory Action Research (PAR) approach that emphasizes the active participation of partners in every stage of the activity, from equipment installation, cultivation training, to digital marketing. The results of the activity show that the application of IoT technology increased catfish production efficiency by up to 30%, while online marketing training increased partners' digital literacy and social media engagement by 250% in the first two weeks. Socially, this activity encouraged the formation of a Budikdamber management group and a digital marketing team that act as local drivers in home-based businesses. This program proves that the integration of appropriate technology and digital marketing can increase the economic independence of rural women while strengthening family food security. Moving forward, activity development can be directed toward diversifying processed fish products and integrating aquaponics systems to create more sustainable economic added value.